Real‐World Use of Normothermic Machine Perfusion in Liver Transplantation: A Multi‐Institutional Experience From the National Organ Perfusion Registry - Alexander R. Cortez; Wei San Loh; Sarah Sheskey; Hillary J. Braun; Aashna Mehta; Christopher Connelly; Austin Schenk; Musab Alebrahim; Raj Patel; Lori A. McLamb; Andrew Barbas; Steven A. Wisel; et al. (Clinical Transplantation, 2026)
ABSTRACT Normothermic machine perfusion (NMP) has enabled increased utilization of high‐risk liver allografts; however, real‐world data describing use, perfusion logistics, and associated outcomes remain limited. We established the National Organ Perfusion Registry (NOPR), a multicenter collaborative registry designed to capture granular perfusion data not available in the national transplant datasets. Adult liver transplant recipients who underwent transplantation using NMP between 2022 and 2024 at nine U.S. centers were included. Registry data were linked to the United Network for Organ Sharing (UNOS) Standard Transplant Analysis and Research files to obtain donor and recipient characteristics and post‐transplant outcomes. Descriptive analyzes were performed to characterize the indications for NMP use, procurement practices, perfusion timing parameters, and early graft outcomes. A total of 545 NMP liver transplants were analyzed, including 282 donations after circulatory death (DCD) and 263 donations after brain death (DBD). DCD was the most common indication for NMP, and its incidence increased substantially during the study period. Perfusion practices varied, including procurement strategy, device use, time from cross‐clamp to NMP initiation, and total perfusion duration. Despite this heterogeneity, early outcomes were favorable, with a 90‐day death‐censored graft failure rate of 1.7%, and no difference between DCD and DBD grafts. Recipients of DCD grafts had a shorter post‐transplant length of stay than DBD recipients. In this multicenter, real‐world cohort analysis, NMP was associated with low rates of early graft failure across diverse centers and perfusion practices. These findings support the feasibility of contemporary NMP use and underscore the importance of continued multicenter evaluation to refine perfusion strategies.